Three-Dimensional Analysis of Initial Brace Correction in the Setting of Adolescent Idiopathic Scoliosis - Almansour, Haidara (J Clin Med, 2019)
The three-dimensional nature of adolescent idiopathic scoliosis (AIS) necessitates a tridimensional assessment and management. Bracing constitutes the mainstay conservative treatment for mild adolescent idiopathic scoliosis. In the literature hitherto, there has been uncertainty regarding the behavior of the spine, pelvis, and vertebral orientations in the context of bracing, especially in the transverse plane. This poses a challenge to healthcare providers, patients, and their families, as brace treatment, although not as invasive as surgery, is laden with medical and psychological complications and could be considered traumatizing. Hence, a thorough understanding of initial three-dimensional spinal behavior in the context of bracing is important. The purpose of this retrospective study was to investigate the immediate 3D impact of Chêneau-type brace. Thirty-eight patients with AIS undergoing Chêneau-type bracing were included. Patients were stratified according to their structural curve topography into thoracic, thoracolumbar, and lumbar groups. 3D reconstruction of the spine using a dedicated biplanar stereoradiography software with and without the brace was performed. The examined anthropometric radiographic measures were pre- to in-brace variations and differences of spinopelvic parameters and vertebral orientations in the coronal, sagittal, and transverse planes. The complex impact of the Chêneau-type brace on different curves in three planes was delineated. In the coronal plane, the Cobb angle was significantly decreased in all types of curves, and the coronal tilt correction was concentrated in specific segments. The impact of the brace in this study on the sagittal profile was variable, including the loss of thoracic kyphosis and lumbar lordosis. In the transverse plane, an axial vertebral rotation change and detorsion above the apex occurred in the thoracolumbar curves. The results from this exploratory study could shed some light on the initial 3D spinal behavior in the context of bracing and may be of beneficial for treating physicians and brace makers.